2008
DOI: 10.1161/atvbaha.107.161174
|View full text |Cite
|
Sign up to set email alerts
|

Chemokines in Atherosclerosis

Abstract: Abstract-The fundamental importance of chemokines for atherogenesis, progression, and destabilization of atherosclerotic plaques is now widely appreciated, but the degree of complexity, specificity, and cooperativity harnessed by these signal molecules to govern atherogenic cell recruitment and homeostasis is still being refined. Since the role of chemokines in atherosclerotic vascular disease has been reviewed in this journal, significant progress has been accomplished in defining the regulation of chemokine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
220
0
7

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 346 publications
(235 citation statements)
references
References 106 publications
8
220
0
7
Order By: Relevance
“…By activating CXCR4, MIF promotes T cell chemotaxis. Accordingly, numerous in vivo studies in proatherogenic mouse models have demonstrated that the MIF-CXCR4 axis critically contributes to atherogenic leukocyte recruitment and atheroprogression (26,(33)(34)(35). The MIF-CXCR4 axis also regulates endothelial progenitor cell migration and cancer cell metastasis (36)(37)(38).…”
mentioning
confidence: 99%
“…By activating CXCR4, MIF promotes T cell chemotaxis. Accordingly, numerous in vivo studies in proatherogenic mouse models have demonstrated that the MIF-CXCR4 axis critically contributes to atherogenic leukocyte recruitment and atheroprogression (26,(33)(34)(35). The MIF-CXCR4 axis also regulates endothelial progenitor cell migration and cancer cell metastasis (36)(37)(38).…”
mentioning
confidence: 99%
“…Platelets and platelet-derived chemokines are important factors during atherogenesis (Gleissner et al 2008, von Hundelshausen et al 2007, Weber 2005, Weber 2008, Zernecke et al 2008). In 2003, Ley et al were able to demonstrate that activated platelets are able to promote atherogenesis (Huo et al 2003).…”
Section: Cxcl4 -A Platelet-derived Chemokine In Atherogenesismentioning
confidence: 99%
“…In fact it seems that each stage of atherosclerosis is characterized by different chemokine-signalling [32] . In the early stages of atherosclerosis, oxLDL induces the expression of CCL2 (or monocyte chemoattractant protein 1) and CX3CL1, by vascular smooth muscle cells (SMCs) and endothelial cells (ECs) [32,33] .…”
Section: Chemokines and Their Receptors In Atherosclerosismentioning
confidence: 99%
“…In fact it seems that each stage of atherosclerosis is characterized by different chemokine-signalling [32] . In the early stages of atherosclerosis, oxLDL induces the expression of CCL2 (or monocyte chemoattractant protein 1) and CX3CL1, by vascular smooth muscle cells (SMCs) and endothelial cells (ECs) [32,33] . CX3CL1 is a structurally unique chemokine that acts both as a chemoattractant and as a potent adhesion molecule through a non-integrin-dependent mechanism [34][35][36] .…”
Section: Chemokines and Their Receptors In Atherosclerosismentioning
confidence: 99%